Available transfer capability (ATC): a review - Hojabri, Mojgan; Hizam, Hashim; Mariun, Norman; Abdullah, Senan Mahmood (Praise Worthy Prize, 2009)
With the advanced development of electrical power markets, large amount of electric power is consumed and transacted which require, accurate determination of Available Transfer Capability (ATC) and broadcasting the ATC information to prevent and relieve transmission congestion effectively. In this paper existing deterministic and probabilistic methods for calculating ATC, are reviewed. Some suggestions for dealing with the technique challenges are given for the future research.